Min Max Model Predictive Control for Polysolenoid Linear Motor - Nguyen Hong Quang; Nguyen Phung Quang; Nguyen Nhu Hien; Nguyen Thanh Binh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The Polysolenoid Linear Motor (PLM) have been playing a crucial role in many industrial aspects because it provides a straight motion directly without mediate mechanical actuators. Some control methods for PLM based on Rotational Motor are applied to obtain several good performances, but position and velocity constraints which are important in real systems are ignored. In this paper, we analysis control problem of tracking position in PLM under state-independent disturbances via min-max model predictive control. The proposed controller brings tracking position error converge to zero and satisfies state including position and velocity and input constraints. The simulation results validity a good efficiency of the proposed controller.